On-line micellar-enhanced spectrofluorimetric determination of rhodamine dye in cosmetics - Wang, Chien Chun (2008)
A simple FI-fluorimetric analytical methodology for the continuous and sequential determination of rhodamine B (RhB) in cosmetic products has been developed and evaluated in terms of sensibility and selectivity. The influence of several surfactant solutions on RhB fluorescence signal has been studied; particular attention was paid in the aggregation behavior of RhB-SDS system. Linear response has been obtained in the range of 1.6 × 10-9 and 1 × 10-6 mol L-1, with a detection limit of 5 × 10-10 mol L-1. The novel technique provides a simple dissolution of sample, on-line filtration with sampling rate higher than 100 samples h-1 and has been satisfactorily applied to the RhB determination in commercial lipsticks.